The breeding work on rice which requires little water at FSBSI “ARC “Donskoy” - P. I. Kostylev; E. V. Krasnova; A. V. Aksenov (Зерновое хозяйство России)
The current paper presents the study results of the upland rice collection in the laboratory of rice breeding and seed pro-duction of the FSBSI “ARC “Donskoy”, on the basis of the JV “Proletarskoye” in the Rostov region. The samples were grown on dry and conventional irrigation backgrounds. The purpose of the study is to use the collection sources of rice drought tolerance to develop productive, early-ripening varieties requiring little water and resistant to a long-term soil and air drought. The col-lection rice samples were studied under intermittent-flow irrigation. There have been identified the samples “Zolotye vskhody” (Russia), “Malovodotrebovatelny” (Uzbekistan), “An-Yun-Ho”, “Ding-Xiang”, “Kontro”, “Khun-Mo”, “Chan-Chun-Man” (China) and others with increased drought tolerance. There have been identified absolute and relative differences in the manifestation of quantitative traits in seven upland samples, among which the samples “Hong-Mo”, “Ding-Xiang”, and “Chan-Chun-Man” turned to be especially prominent. The maximum integral index of stability was identified in the sample “Hong-Mo” (69.1%), and the minimum one was identified in the sample “An-Yun-Ho” (53.6%). The largest ratio of the value of the trait in dry and conventional conditions on average for all varieties was 1000 kernels (97.1%), then in descending order there were “plant height” (81.7%), “panicle length” (76.8%), “productivity” (63.4%), “kernel weight per panicle’ (42.3%), “number of full kernels per panicle” (38.1%) and “empty spikelets per panicle” (21.6%). Thus, “kernels weight” decreases to the least extent, and “number of spikelets per panicle” reduces to the largest extent. There were carried out the crossings of upland samples with the best varieties in four combinations. The rice samples were propagated for further study under intermittent-flow irrigation. The identified rice samples have been included in the breeding program to develop rice varieties which require little water for the conditions of the Rostov region.